2012
DOI: 10.2147/jpr.s31754
|View full text |Cite
|
Sign up to set email alerts
|

Intensive interdisciplinary outpatient pain management program for chronic back pain: a pilot study

Abstract: BackgroundChronic back pain is relatively resistant to unimodal therapy regimes. The aim of this study was to introduce and evaluate the short-term outcome of a three-week intensive multidisciplinary outpatient program for patients with back pain and sciatica, measured according to decrease of functional impairment and pain.MethodsThe program was designed for patients suffering from chronic back pain to provide intensive interdisciplinary therapy in an outpatient setting, consisting of interventional injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…However, there are some reports which highlight a need for strengthened collaboration between pharmacists and prescribers, in order to [44]. Increasingly, evidence around chronic back pain management support a patient-centered approach to care within a multidisciplinary framework, as it is unlikely complex cases can be adequately managed by a single HCP acting independently [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some reports which highlight a need for strengthened collaboration between pharmacists and prescribers, in order to [44]. Increasingly, evidence around chronic back pain management support a patient-centered approach to care within a multidisciplinary framework, as it is unlikely complex cases can be adequately managed by a single HCP acting independently [45].…”
Section: Discussionmentioning
confidence: 99%
“…Artner et al analyzed the short-term outcome of a 3-week intensive multidisciplinary outpatient program for patients suffering from back pain and sciatica retrospectively 10. The intensive treatment consisted of interventional injection techniques (eg, epidural, periradicular and facet joint injections) with a frequency of up to 8 injections per patient and additional multiple treatment approaches such as modification of analgesic medication, ergotherapy, massage therapy, back education, transcutaneous electrical nerve stimulation and aquatraining.…”
Section: Dear Editormentioning
confidence: 99%
“…However it was used with increased frequency over the time period observed. Baseline and outcome parameters were assessed using only the Numeric Rating Scale (NRS) and Oswestry Disability Index (ODI) 10. They concluded that the short-term results of their treatment program were clinically significant in improving pain as well as in functionality.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations